High frequency of resistance, lack of clinical benefit, and poor outcomes in capreomycin treated South African patients with extensively drug-resistant tuberculosis. - Elize Pietersen; Jonny Peter; Elizabeth Streicher; Frik Sirgel; Neesha Rockwood; Barbara Mastrapa; Julian Te Riele; Malika Davids; Paul van Helden; Robin Warren; Keertan Dheda (PLoS ONE, 2015)
There are limited data about the epidemiology and treatment-related outcomes associated with capreomycin resistance in patients with XDR-TB. Capreomycin achieves high serum concentrations relative to MIC but whether capreomycin has therapeutic benefit despite microbiological resistance remains unclear.We reviewed the susceptibility profiles and outcomes associated with capreomycin usage in patients diagnosed with XDR-TB between August 2002 and October 2012 in two provinces of South Africa. Patients whose isolates were genotypically tested for capreomycin resistance were included in the analysis.Of 178 XDR-TB patients 41% were HIV-infected. 87% (154/178) isolates contained a capreomycin resistance-conferring mutation [80% (143/178) rrs A1401G and 6% (11/178) were heteroresistant (containing both the rrs A1401G mutation and wild-type sequences)]. Previous MDR-TB treatment, prior usage of kanamycin, or strain type was not associated with capreomycin resistance. 92% (163/178) of XDR-TB patients were empirically treated with capreomycin. Capreomycin resistance decreased the odds of sputum culture conversion. In capreomycin sensitive and resistant persons combined weight at diagnosis was the only independent predictor for survival (p=<0.001). By contrast, HIV status and use of co-amoxicillin/clavulanic acid were independent predictors of mortality (p=<0.05). Capreomycin usage was not associated with survival or culture conversion when the analysis was restricted to those whose isolates were resistant to capreomycin.In South Africa the frequency of capreomycin conferring mutations was extremely high in XDR-TB isolates. In those with capreomycin resistance there appeared to be no therapeutic benefit of using capreomycin. These data inform susceptibility testing and the design of treatment regimens for XDR-TB in TB endemic settings.